Theoretical Problems of Cartography: The Case of Vilnius - Milerius, Nerijus (Problemos, 2004)
The article deals with one of the most controversial subject of contemporary urban thought, namely, theoretical aspects of cartography. The part of departure of the article is well-known Jean Baudrillard’s dictum that nowadays a map precedes a territory. It is argued that history of cartography not only confirms this controversial dictum but even radicalises it. Historians of cartography see a map not only as product of scientific modelling but also as closely tied to various historical and cultural contexts that, in turn, actively participate in the process of mapping. Examples of Vilnius map are examined in the article. Finally, the article seeks to answer which parameters of Vilnius are exposed in recent procedures of mapping.
Keywords: cartography; map; modelling; deconstruction.